2021
DOI: 10.3390/met11020184
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Dissolution and Precipitation Behavior of Self-Designed (NbTi)C Nanoparticles Addition in 1045 Steel

Abstract: Self-designed (NbTi)C nanoparticles were obtained by mechanical alloying, predispersed in Fe powder, and then added to 1045 steel to obtain modified cast steels. The microstructure of cast steels was investigated by an optical microscope, scanning electron microscope, X-ray diffraction, and a transmission electron microscope. The results showed that (NbTi)C particles can be added to steels and occur in the following forms: original ellipsoidal morphology nanoparticles with uniform dispersion in the matrix, cub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…It can be seen from the microstructure that the sizes of the austenite and carbides decreased after adding (NbTi)C particles (Figure 1), and the main reason for this structural transformation may be because the (NbTi)C particles can be used as the nucleation core of austenite, which increases the nucleation probability of austenite. Previous studies have confirmed that the addition of (NbTi)C particles can host the nucleation position of austenite in carbon steel [18][19][20], and that the (NbTi)C particles can hinder the growth of primary austenite grains. In addition, research has shown that the added particles also have a certain refining effect on carbides in cast iron [21,22].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…It can be seen from the microstructure that the sizes of the austenite and carbides decreased after adding (NbTi)C particles (Figure 1), and the main reason for this structural transformation may be because the (NbTi)C particles can be used as the nucleation core of austenite, which increases the nucleation probability of austenite. Previous studies have confirmed that the addition of (NbTi)C particles can host the nucleation position of austenite in carbon steel [18][19][20], and that the (NbTi)C particles can hinder the growth of primary austenite grains. In addition, research has shown that the added particles also have a certain refining effect on carbides in cast iron [21,22].…”
Section: Discussionmentioning
confidence: 80%
“…Before smelting, the crucible was wrapped with a glass fiber cloth with a temperature resistance of 2000 • C to prevent the melt flowing out and damaging the cooling system due to the crack of the crucible during the smelting process. The preparation process of self-designed (NbTi)C particles has been introduced in detail in the literature [18][19][20]. Commercially available Nb powder, Ti powder (purity 99.5 wt % and particle size ≤ 40 µm), and graphite powder (purity 99.5 wt % and particle size ≤ 4 µm) were used as raw materials.…”
Section: Methodsmentioning
confidence: 99%
“…Take the sample at half the radius of the ingot, observe the added (NbTi)C particles with FEI Tecnai G 2 F30 TEM, and identify the composition and structure of the particles through the attached energy-dispersive spectrometer (EDS) and selected area diffraction pattern (SADP). The detailed experimental method, process, and conclusion have been published in previous articles. …”
Section: Methodsmentioning
confidence: 99%